Peningkatan Hasil Belajar Tematik Terpadu menggunakan Model Discovery Learning di Kelas IV - Oktamia, Yulia; S, Farida (Universitas Negeri Padang, 2022)
The purpose of this study is to describe the improvement of student learning outcomes in integrated thematic learning using the Discovery Learning Model. This type of research is Classroom Action Research (CAR) using quantitative and qualitative approaches. The place of the study was the 13 Batu Gadang State Elementary School, Padang City. The results of this study indicate: a) RPP cycle 1 meeting 1 obtained an average of 77,77%, cycle 1 meeting 2 obtained an average of 86.11% (good) and cycle II 94% (very good), b) Implementation on the teacher aspect the first cycle meeting 1 obtained an average of 79.68% (good) and the second cycle 90.6% (very good), while the implementation of aspects of the first cycle students with an average of 79.68% (good), and the second cycle 90 , 6% (very good), c) Assessment of students in improving learning outcomes in the first cycle obtained with an average of 81.2 and the second cycle with an average of 86.6. Based on these results it can be concluded that the Discovery Learning model can improve student learning outcomes in integrated thematic learning.